2013
DOI: 10.1109/tnano.2013.2284777
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Dipole Coupled Multiferroic Nanomagnets in the Presence of Thermal Noise: Reliability of Nanomagnetic Logic

Abstract: The stress-induced switching behavior of a multiferroic nanomagnet, dipole coupled to a hard nanomagnet, is numerically studied by solving the stochastic Landau-Lifshitz-Gilbert equation for a single-domain macrospin state. Different factors were found to affect the switching probability in the presence of thermal noise at room temperature: 1) dipole coupling strength, 2) stress levels, and 3) stress withdrawal rates (ramp rates). We report that the thermal broadening of the magnetization distribution causes l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…The error rate is an important feature in the ME memory. The simulation and calculation displayed that the error rate in ME switching was high, but could be reduced via modest theoretical design [ 121 , 122 , 123 ]. The relevant experimental outcome of error rate is waiting to be verified.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…The error rate is an important feature in the ME memory. The simulation and calculation displayed that the error rate in ME switching was high, but could be reduced via modest theoretical design [ 121 , 122 , 123 ]. The relevant experimental outcome of error rate is waiting to be verified.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…The magnetisation dynamics of any nanomagnet is described by the Landau–Lifshitz–Gilbert equation [27] right leftthickmathspace.5emdMdt=γM×bold-italicHeffαγMnormalsfalse[bold-italicM×false(bold-italicM×Hnormalefffalse)false] where H eff is the effective magnetic field on one nanomagnet, accordingly [28] Hnormaleff=1μ0VdEdM+Hnormalthermal In (1) and (2), M s is the saturation magnetisation of the magnetostrictive layer, μ 0 is the permeability of vacuum, γ is the gyromagnetic ratio, V is the volume of the nanomagnet, α is the Gilbert damping factor. The total energy of any element due to the shape anisotropy, stress anisotropy and dipole coupling energy with the neighbour nanomagnet is given as [18] E=Enormaldipole+Enormalshape+Enormalstress Let θ be the polar angle and φ is the azimuthal angle of the magnetisation vector (see Fig.…”
Section: Modelling Of Majority Gatementioning
confidence: 99%
“…[7] studied room-temperature error probabilities in dipole-coupled NML logic clocked with magnetic fields instead of strain and found them to be impractically high (> 1%). We showed that SML with intermagnet dipole-coupling is similarly error prone [8] owing to the out-of-plane excursion of the magnetization vector during switching that produces a detrimental torque which hinders correct switching [9]. Here, we will address the question of improving the reliability of dipole-coupled SML by making information transfer between two multiferroic nanomagnets (NMs) interacting via dipole coupling more robust.…”
Section: Introductionmentioning
confidence: 99%